Urbanization Policy. Planning Essays. (Urbanisierungspolitik. Planungsessays.) - (:unkn) unknown (My University, 1973)
Das Heft enthält folgende Beiträge The impact of national development policies on urbanization South and South-east Asia (Gerald M. Desmond), Planning for urbanization in emerging Nations (Adepoju G. Onibokun), Urban development in less developed countries A strategy for urban planning (Warren Seyfried).
Keywords: Urbanisierung; Entwicklungsland; Stadtentwicklung; Stadtplanung; Planung